Стереотипы предпринимательства в массовом сознании: гендерный анализ - Суковатая, В. (Социология: теория, методы, маркетинг, 2001)
The article presents analysis of the entrepreneurship stereotypes in the mass consciousness of Ukrainians. There are discussed the pattern of women’s life represented in soviet and post-soviet public discourse, as well as the anti-feminist myths typical in the mass media. The subjective feminine images constructed by women in order to interpret their lives, professional, family and marriage status are described. As a result, the author concludes that many businesswomen consider their self-realization in business as the ‘cultural trans-regression’ form and way to overcoming gender borders.